Industrial location policy : the Indian experience - Sekhar A. Uday (Washington, D.C. : The World Bank, 1983)
This paper probes into the working and impact of individual location policies, and demonstrates certain serious deficiencies and lacunae in the justification, design and implementation of many of them.
Includes bibliographical references. p: 109-110
osa 08/11/2018
Loans
Keywords: India--Industries--Location.; India